PERANAN HUMAS SEKRETARIAT DAERAH PROVINSI KALIMANTAN SELATAN SEBAGAI MEDIA KOMUNIKASI ANTARA MASYARAKAT DAN PEMERINTAH PROVINSI KALIMANTAN SELATAN - Zainal Hakim; M. Yunus Jarmie; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The importance of communication in human life must be recognized becausehumans are social beings. We are social creatures and heavily depend on our abilityto communicate to make our way through the world.This is a descriptive-qualitative research. The data and the informationwere taken from the documents that were appropriate to the subjects and the objectsof research and conducted through the depth interview of the informants.The analysis showed that the strategy undertaken by the Public Relation ofthe Government of South Kalimantan Province, especially in the dissemination ofgovernment police in the are is still not optimal given the existing strategy conceptis still not fully refers to the concept of public relations that is only limited to thecollection/processing of data, publication/dissemination and assessment/evaluationalthough in terms of cooperation with journalists was conducted by PR, but for theimplementation of the effective response to various policies of govermentregulations can not be implemented yet maximal.South Kalimantan in order to carry out PR duties and obligations in anoptimal, ideally public relations activities are directed to the Public Relationsactivities. Structurally, the Office of Public Relations and information equivalen tothe ranks of the head is placed within the province of South Kalimantan SKPD For itis first necessary to be done in order to become good public relations personnel areproviding adequate functional. Required the addition of facilities and infrastructureare adequate in quantity and quality.